Emergency care usage and longevity have opposite effects on health insurance rates. Issue 1 (9th January 2017) - Piulachs, Xavier; Alemany, Ramon; Guillen, Montserrat
Abstract : Purpose: This paper aimed to study the price of health insurance for individuals aged 65 years and over. Design/methodology/approach: A sample of private health policyholders in Spain is analysed. Joint models are estimated for men and women, separately. A log-linear model of the transformed cumulated number of claims associated with emergency room occupation, ambulance use and hospitalization is estimated, together with a proportional hazard survival model. Findings: The association between the longitudinal process of severe medical care and the survival time process is positive and highly significant for both men and women. An increase in the price of health insurance because of the effect of a larger number of emergency care demand events is slightly offset by the decrease in expected longevity. Research limitations/implications: The effect of an increase in the number of claims is small compared to the reduction in survival, so age still plays a central role in ratemaking. Practical implications: High rates of health insurance for elderly insureds should be compensated with younger insureds in the portfolio. Social implications: Affordable health insurance premiums for elderly people are difficult to obtain only with strict actuarial principles. Originality/value: The proposed methodology allows dynamic rates to be designed, so that the price of health insurance can change as new usage information becomes available.